1998
DOI: 10.1183/09031936.98.12051130
|View full text |Cite
|
Sign up to set email alerts
|

Lung function and exercise capacity in thalassaemia major

Abstract: Lung function abnormalities in thalassaemia major are various and complex; however, patients still die from cardiac lesions. This study aimed to investigate pulmonary and cardiac involvement at an early stage in thalassaemic patients and study their respective implications at rest and during exercise. Ten patients (five adults and five children) with thalassaemia major were investigated by echocardiography, lung function and exercise testing a few days after transfusion. All have had regular transfusions and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…We found that patients with TM have decreased aerobic capacity (decreased V O2 max), in agreement with the literature [4][5][6][7][8][9][10][11][12][13]. Only one article did not find decreased exercise capacity in TM patients.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We found that patients with TM have decreased aerobic capacity (decreased V O2 max), in agreement with the literature [4][5][6][7][8][9][10][11][12][13]. Only one article did not find decreased exercise capacity in TM patients.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to previous studies, we found that exercise was partially limited by abnormal V O2 -HR relationships [5][6][7]11]. O 2 pulse is equal to V O2 divided by HR, which is equivalent to the products of stroke volume, hemoglobin, and oxygen extraction.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…But this treatment has some complications, such as progressive iron deposition in vital organs, which impairs their functions [3]. There are some debates about abnormalities of respiratory function and causes of its dysfunction [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
mentioning
confidence: 99%